Transformations? Skilled Change Agents Influencing Organisational Sustainability Culture. (22nd January 2016) - Davis, Keith; Boulet, Mark
Abstract: Training employees in sustainability knowledge and skills is considered a vital element in creating a sustainability culture within an organisation. Yet, the particular types of training programs that are effective for this task are still relatively unknown. This case study describes an innovative workplace training program using a 'head, hands, heart and feet' learning framework to create skilled change agents among employees, in order to influence organisational sustainability culture. Utilising a dialogic inquiry methodology (Most Significant Change), as well as Mezirow's phases of transformative learning and Schein's organisational culture framework, this study considers the training program's impact on both participants and organisational sustainability culture. While transformative learning impacts for participants were identified, questions remain as to the overall impact of the program on the organisation's sustainability culture. Considering training participants as 'seeds of influence' as opposed to wholly responsible for organisational culture might provide new perspectives to these questions.